Clinical and morphological features of infective endocarditis of native and prosthetic heart valves - U. M. Shadrina; M. A. Korzhova; N. O. Litskevich; I. V. Antonova; M. L. Gordeev; E. A. Demchenko; L. B. Mitrofanova; O. B. Irtyuga (Российский кардиологический журнал, 2023)
Aim. To evaluate clinical and morphological data of infective endocarditis (IE) of native and prosthetic heart valves.Material and methods. This retrospective cohort study included 354 patients that had signs of IE according to pathological study of surgical material from native valves and prosthetic heart valves. The patients were divided into two groups: the first group included patients with native valve IE (n=328), while the second group — with prosthetic valve IE (n=26).Results. Among patients with native valve IE, aortic (AV) and mitral valve (MV) IE was recorded in 67,6% and 20,7%, respectively. In the group of patients with prosthetic IE, AV IE also predominated — 57,7% vs 26,9% in MV IE. In the majority of patients in the first group, secondary IE was detected (68,9%). The development of IE in the presence of bicuspid AV (BAV), degenerative AV disease, and rheumatic valve disease was revealed in 40,7%, 31,4% and 6,7%, respectively. In the group of patients with native valve IE, subactive IE was most often detected — in 38,4%, while in 7,1% — signs of process remission were detected. In the group of patients with prosthetic valve IE, IE with moderate activity was detected more often than in the group of patients with native valve IE (42,3% vs 26,8%, p=0,042). In the group of patients with prosthetic valve IE, the presence of colonies of microorganisms and neutrophilic infiltration in the histological material was somewhat more common, while in patients with native valve IE there was a tendency towards a higher percentage of necrosis in the studied material (42,4% vs 38,5%, p>0,05).Conclusion. This work confirms changes in the epidemiological characteristics of patients with IE. A high frequency of subactive forms of IE was noted according in patients with native valve IE, which requires individual approach to antibacterial therapy depending on the pathomorphological IE activity.